Challenges and Limitations of Targeting the Keap1-Nrf2 Pathway for Neurotherapeutics: Bach1 De-Repression to the Rescue - Hushpulian, Dmitry M.; Ammal Kaidery, Navneet; Ahuja, Manuj; Poloznikov, Andrey A.; Sharma, Sudarshana M.; Gazaryan, Irina G.; Thomas, Bobby (Frontiers in Aging Neuroscience, 2021)
The Keap1-Nrf2 signaling axis is a validated and promising target for cellular defense and survival pathways. This minireview discusses the potential off-target effects and their impact on future drug development originating from Keap1-targeting small molecules that function as displacement activators of the redox-sensitive transcription factor Nrf2. We argue that small-molecule displacement activators, similarly to electrophiles, will release both Nrf2 and other Keap1 client proteins from the ubiquitin ligase complex. This non-specificity is likely unavoidable and may result in off-target effects during Nrf2 activation by targeting Keap1. The small molecule displacement activators may also target Kelch domains in proteins other than Keap1, causing additional off-target effects unless designed to ensure specificity for the Kelch domain only in Keap1. A potentially promising and alternative therapeutic approach to overcome this non-specificity emerging from targeting Keap1 is to inhibit the Nrf2 repressor Bach1 for constitutive activation of the Nrf2 pathway and bypass the Keap1-Nrf2 complex.